A metal ion release study of CoCrMo exposed to corrosion and tribocorrosion conditions in simulated body fluids - Espallargas, N.; Torres, C.; Muñoz, A.I. (Wear, 2015)
Several studies have investigated the presence of metal ions in different human fluids (i.e. blood, urine, serum and plasma) of patients using CoCrMo bearing implants. The general conclusion is that the degradation mechanisms of the implants (the joint action of biocorrosion and wear) lead to an increase of dissolved metals and particles leading to implants failure and tissue inflammation. However, the levels of metallic ions in those fluids can vary depending on the involved degradation mechanism of the implant (corrosion or tribocorrosion). Having a tool able to identify the origin of the metal ion concentration in patients using metal bearing implants could allow faster and easier clinical treatments and failure detection. This work has investigated the metal ion release of a low carbon CoCrMo subjected to different electrochemical and tribocorrosion conditions in NaCl, phosphate buffer solution (PBS) and PBS with protein (albumin) at the human body conditions of 37°C. Cobalt is the most concentrated ion and has the largest concentration ratio in all testing conditions, with the exception of the corrosion tests in PBS with albumin. Albumin drastically increases the molybdenum concentration in the electrolyte after corrosion tests at applied potentials below the transpassive region of the alloy. In the tribocorrosion tests, an increase of metal ion concentration with potential was found, while this effect was not observed in the corrosion tests, thus electrode potential variations are critical for metal ion release of CoCrMo alloys under tribocorrosion conditions. Combining ICP-MS analysis with electrochemical testing gives mechanistic information on the involved redox reactions, oxide formation and amount of wear debris in corrosion and tribocorrosion situations of biomedical alloys. This is needed for the interpretation of the in vivo data. •First time complete measure of metal ion release CoCrMo in simulated body fluids.•Albumin increases Mo concentration during electrochemical tests.•Identification of the origin of metals according to the degradation mechanism.•Mass balance mechanism for tribocorrosion and quantification of the debris.